2011
DOI: 10.1001/archoto.2011.131
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Indomethacin on Paclitaxel Sensitivity and Apoptosis in Oral Squamous Carcinoma Cells<subtitle>The Role of Nuclear Factor–κB Inhibition</subtitle>

Abstract: Paclitaxel has the capacity to activate NF-κB in oral squamous carcinoma cells. Indomethacin can reverse this activation to decrease cell proliferation and increase apoptosis. Treatment strategies that combine paclitaxel with indomethacin may have therapeutic benefits attributable to paclitaxel chemosensitization through NF-κB inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Paclitaxel induces apoptosis through the activation of JNK [31], while the phosphorylation of ERK [32,33], Bad [34] and IκBα [35] results in paclitaxel resistance. Our study revealed that treatment with paclitaxel increased the phosphorylation levels of JNK, IκBα, Bad and ERK, which was in line with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel induces apoptosis through the activation of JNK [31], while the phosphorylation of ERK [32,33], Bad [34] and IκBα [35] results in paclitaxel resistance. Our study revealed that treatment with paclitaxel increased the phosphorylation levels of JNK, IκBα, Bad and ERK, which was in line with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence exists showing that SLPI inhibits NF-κB[32], [33], although this has not been demonstrated in models of oral cancer. Given this evidence, we sought to investigate whether or not SLPI decreases NF-κB activity in MSK-Leuk1 cells, using a luciferase-based reporter assay[34]. We treated the transfected MSK Leuk1 cells with two different concentrations of pure SLPI peptide (20 ug/mL and 40 ug/mL), and measured NF-κB at different times after treatment ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, ROS also plays an important role in the ATO-induced apoptosis and cell death [28]. Consistent with this hypothesis, accumulating evidence indicates that L-buthionine-sulfoximine (BSO), a drug that depletes intracellular glutathione (GSH) and generates ROS, can sensitize the lung cancerous cells to ATO-induced cell death [24, 42, 4446]. Moreover, ROS can activate ERK1/2 pathway [47] as well as p38 kinase [47, 48].…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that indomethacin induces apoptosis in vivo [38] and in vitro in some cancerous cells including lung [7, 8], colon [39, 40], and leukemia [41]. In this report, production of ROS has been mentioned as the main mechanism of apoptotic effect [42, 43]. Besides, ROS also plays an important role in the ATO-induced apoptosis and cell death [28].…”
Section: Discussionmentioning
confidence: 99%